2021
DOI: 10.3390/metabo11010031
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Biogenic Amines in Different Cheese Varieties Obtained from the Korean Domestic and Retail Markets

Abstract: To evaluate the safety and risk assessment of cheese consumption in the Republic of Korea, sixty cheese samples purchased from the farmstead and retails markets (imported) were analyzed for their biogenic amine (BA) contents. The BA profiles and quantities of eight amines (tryptamine, 2-phenylethylamine, putrescine, cadaverine, histamine, tyramine, spermidine, and spermine) were determined using high-performance liquid chromatography (HPLC). Spermine was the only amine detectable in all the samples. The BAs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…The European Union has established certain regulations on histamine with the maximum levels of 100 mg/kg ( Sun et al, 2016 ). According to a previous report, the established maximum limits were 800 mg/kg for tyramine ( Ercan et al, 2019 ) and 30 mg/kg for phenethylamine, respectively ( Kandasamy et al, 2021 ). Seven kinds of biogenic amines including tyramine, putrescine, cadaverine, spermidine, tryptamine, phenylethylamine, and spermine were detected in the control ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The European Union has established certain regulations on histamine with the maximum levels of 100 mg/kg ( Sun et al, 2016 ). According to a previous report, the established maximum limits were 800 mg/kg for tyramine ( Ercan et al, 2019 ) and 30 mg/kg for phenethylamine, respectively ( Kandasamy et al, 2021 ). Seven kinds of biogenic amines including tyramine, putrescine, cadaverine, spermidine, tryptamine, phenylethylamine, and spermine were detected in the control ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the decarboxylation of some amino acids in cheese leads to the formation of biogenic amines (BA), nonvolatile amines with important physiological effects in humans (Gaya et al 2005). Many factors contribute to the presence and accumulation of BA, such as availability of free amino acids, pH, raw, salt-in-moisture level, temperature, redox potential bacterial density and, primarily, the presence of microorganisms (Schirone et al 2012;Pleva et al 2014;Kandasamy et al 2021). Under normal conditions, exogenous BA ingested with food are rapidly detoxified by the action of amine oxidases.…”
Section: Introductionmentioning
confidence: 99%
“…Many analytical methods were used to assess biogenic amines such as ion-exchange chromatography with colorimetric detection, GC-MS, HPLC-MS/MS, and HPLC-DAD (Rabie et al 2011;Kandasamy et al 2021;Loizzo et al 2013) and capillary electrophoresis coupled with contactless conductivity detection (Adımcılar et al 2018). Hazardous levels (> 100 mg/kg) of biogenic amines including histamine and tyramine were reported in Mesh and blue cheese in Egypt using ion-exchange chromatography-colorimetric detector, based on protein separation according to their surface charge.…”
Section: Sample Pre-treatment Methodsmentioning
confidence: 99%
“…Their levels generally were in the order of milligrams per kilogram; however, they may reach 2 g/kg (Linares et al 2011). It was reported that the maximum limits of biogenic amines in foods for human consumption as histamine, tyramine, phenylethylamine, and total BAs is around 50-100, 100-800, 30, and 200-1000 mg/kg, respectively (Ec 2003;Kandasamy et al 2021).…”
Section: Types Of Hazardsmentioning
confidence: 99%